Method for detecting dislocation slip line of silicon single crystal

Through chromium-free liquid corrosion methods and auxiliary detection technology, the problem of using chromium-containing corrosion liquid in the prior art is solved and the problem of polluting the environment is realized, and accurate detection of silicon single crystal dislocation slip lines and environmentally friendly production technology are realized.

CN119780115AActive Publication Date: 2025-04-08SHANDONG GRINM SEMICON MATERIALS CO LTD +1

Patent Information

Application Number
CN202411891799.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-08
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

When the existing chemical corrosion methods are used to detect the slip lines of single crystal dislocations, they mainly use chromium-containing corrosion liquid, which is difficult to deal with and pollute the environment, and lacks environmentally friendly alternative methods.

Method used

The chromium-free liquid corrosion method is used to control the corrosion rate by regulating the concentration and volume ratio of the mixed solution of nitric acid and hydrofluoric acid, and combining visual lamps and X-ray diffraction morphology (XRT), the silicon single crystal dislocation slip line is accurately identified and detected.

Benefits of technology

Accurate detection of <100> crystalline silicon single crystal dislocation slip lines with large diameter doped B is achieved, which is easy to operate, environmentally friendly, and reduces pollution risks and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119780115A_ABST
    Figure CN119780115A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting a dislocation slip line of a silicon single crystal, which is particularly suitable for detecting the dislocation slip line of the silicon single crystal with the diameter of more than 300mm and the doping agent of 1t of B element. 100 gt; and detecting the dislocation slip line of the crystal orientation silicon single crystal. The method comprises the following steps: prototype; 100 gt; after drawing of the crystal orientation silicon single crystal is completed, a sample with the thickness of 2-10 mm is cut out, and the sample is cleaned with deionized water; a mixed solution is used for corroding the sample, the sample is immersed into the mixed solution of nitric acid with the concentration being 65-68% and hydrofluoric acid with the concentration being 45-49%, the volume ratio of hydrofluoric acid to nitric acid in the mixed solution is HF: HNO3 = 10: 1, and the soaking time is 30-40 min; a visual inspection lamp is used for judging a corroded result, and the position and the length of a dislocation slip line are determined; and carrying out auxiliary judgment on the sample by using X-ray diffraction morphology. The detection method is simple and convenient to operate and easy to implement, chromium-free liquid corrosion is adopted, the position and the length of the dislocation slip line are determined under an accent light, interference factors can be eliminated, and the dislocation slip line can be accurately recognized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of direct-pull silicon single crystal detection, and relates to a method for detecting dislocation slip lines of silicon single crystals. Background Art

[0002] Dislocation is an internal microscopic defect of a crystal material, that is, a local irregular arrangement of atoms (crystallographic defect). Dislocation is a line defect and can be regarded as the boundary between the slipped part and the non-slipped part in the crystal. Its existence has a significant impact on the properties of silicon crystal materials, especially the mechanical properties.

[0003] Chemical etching is one of the most effective means to study silicon wafer crystal defects. Different surface states of single crystals lead to different corrosion rates, thus revealing crystal dislocation slip lines. However, the chemical etching methods currently used mainly contain chromium, which is difficult to handle and pollutes the environment. The development of new single crystal dislocation slip detection methods is urgently needed. Chromium-free etching liquid came into being. By adjusting parameters, the corrosion rate of the single crystal surface is controlled, and different states are presented on the single crystal surface. This etching method is expected to become an environmentally friendly production technology. Summary of the invention

[0004] The purpose of the present invention is to provide a method for detecting dislocation slip lines of silicon single crystals, which is suitable for large-diameter B-doped <100> The detection method of dislocation slip lines of silicon single crystals with different crystal orientations can accurately identify dislocation slip lines and is environmentally friendly.

[0005] To achieve the above object, the present invention adopts the following technical solutions: A method for detecting dislocation slip lines of a silicon single crystal comprises the following steps: (1) Native <100> After the crystal orientation silicon single crystal is pulled, a sample with a thickness of 2-10 mm is cut and cleaned with deionized water; (2) Corrode the sample using a mixed solution, immerse the sample in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, wherein the volume ratio of hydrofluoric acid to nitric acid in the mixed solution is HF:HNO3=10:1, and the immersion time is 30-40 min; (3) Use a visual inspection light to determine the corrosion results and the location and length of the dislocation slip line; (4) Use X-ray diffraction topography (XRT) to assist in the identification of samples.

[0006] The detection method of the present invention is particularly suitable for the diameter of more than 300mm, the dopant is B element <100> Detection of dislocation slip lines in silicon single crystals with different crystal orientations.

[0007] As an embodiment of the present invention, in the step (1), the thickness of the sample cut is 4-10 mm.

[0008] As an embodiment of the present invention, in the step (3), a visual inspection light with a light intensity ≥ 7 klux is used for visual inspection.

[0009] As an embodiment of the present invention, in the step (4), due to the limitation of the XRT fixture, there is a sample thickness detection limit when testing the sample, that is, the upper limit of the thickness is 3 mm. Therefore, when the sample thickness is less than 3 mm, XRT is used to determine the position and length of the dislocation slip line, and the results are compared with the visual inspection results of the physical sample.

[0010] The advantages of the present invention are: The detection method of the present invention is simple to operate and easy to implement. The chromium-free solution is used to etch the diameter of the sample larger than 300 mm, and the dopant is the B element. <100> For silicon single crystals with different crystal orientations, during the etching process, the appropriate etching solution and etching time are selected, and the position and length of the dislocation slip line are determined under a strong light. This can eliminate interference factors and accurately identify the dislocation slip line. At the same time, by comparing it with the XRT morphology diagram, the goals of environmental friendliness, cost reduction and efficiency improvement can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 (a) ~ Figure 1 (e) The results of visual inspection of dislocation slip lines after corrosion in Comparative Examples 1 to 3, Example 1, and Comparative Example 4 are shown in order.

[0012] Figure 2 (a) ~ Figure 2 (e) The results of visual inspection of dislocation slip lines under a lamp after corrosion of Comparative Examples 5-7 and Examples 2-3 are shown respectively.

[0013] Figure 3 (a) ~ Figure 3 (e) are the results of visual inspection of dislocation slip lines after corrosion in Comparative Examples 8 to 11 and Example 4, respectively.

[0014] Figure 4 (a) Figure 4 (b) are microscope images of the silicon single crystal samples after etching in Comparative Example 8 and Example 4, respectively.

[0015] Figure 5 (a) Figure 5 (b) are the visual inspection results of the dislocation slip lines under the lamp after corrosion in Example 5 and the scanned XRT morphology results.

[0016] Figure 6 (a) ~ Figure 6(d) Visual inspection results of the silicon single crystal samples after etching in Comparative Example 12, Example 6, Example 7, and Comparative Example 13, respectively. DETAILED DESCRIPTION

[0017] In order to more clearly describe the technical solution of the present invention, the present invention is described in detail below in conjunction with the accompanying drawings and embodiments. All of the above are technologies related to the present case, and the embodiments described are part of the embodiments of the present invention, but do not mean to limit the scope of protection of the present invention.

[0018] 1. Select a section of 8-inch B-doped <100> The silicon single crystal rod with a crystal orientation is continuously cut into silicon single crystal samples with a thickness of 2.5±0.2 mm. The sample numbers of this section of the single crystal rod from the tail to the head are 1 to 5, and they are cleaned with deionized water. Samples 1 to 5 are etched in accordance with the etching processes of the following comparative examples 1 to 4 and embodiment 1.

[0019] Comparative Example 1 The sample is immersed in a mixed solution of hydrofluoric acid and chromium trioxide aqueous solution with a concentration of 45-49%. The specific ratio and immersion time are based on the Schimmel etching solution in the GB / T 1554-2009 (current) standard for corrosion.

[0020] Comparative Example 2 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 5:1 solution, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0021] Comparative Example 3 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 8:1 solution, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0022] Example 1 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 10:1 solution, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0023] Comparative Example 4 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 15:1 solution, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0024] like Figure 1 As shown, Figure 1 (a) shows the appearance of dislocation slip lines under a visual inspection lamp after corrosion in Comparative Example 1; Figure 1 (b) shows the results of the visual inspection of dislocation slip lines after corrosion in Comparative Example 2. Figure 1 (c) shows the appearance of dislocation slip lines under a visual inspection lamp after corrosion in Comparative Example 3; Figure 1 (d) shows the results of the visualization of dislocation slip lines under a visual inspection lamp after corrosion in Example 1. Figure 1 (e) shows the results of the visual inspection of dislocation slip lines after corrosion in Comparative Example 4.

[0025] As can be seen from the figure, the degree of appearance of the dislocation slip line in Example 1 is comparable to the degree of appearance of the dislocation slip line of chromium liquid corrosion required by the national standard of Comparative Example 1. As the HF:HNO3 (volume ratio) decreases, the clarity of the dislocation slip line in Comparative Example 2 and Comparative Example 3 is poor and not obvious. As the HF:HNO3 (volume ratio) increases, the clarity of the dislocation slip line in Comparative Example 4 is poor and not obvious. Therefore, when the ratio in Example 1 is HF:HNO3 (volume ratio) = 10:1, the degree of appearance of the dislocation slip line is better.

[0026] 2. Select a section of 8-inch B-doped <100> The silicon single crystal rod with a crystal orientation is continuously cut into silicon single crystal samples with a thickness of 2.5±0.2 mm. The sample numbers of this section of the single crystal rod from the tail to the head are 1 to 5, and they are cleaned with deionized water. Samples 1 to 5 are etched in accordance with the etching processes of the following comparative examples 5 to 7 and embodiments 2 to 3.

[0027] Comparative Example 5 The sample is immersed in a mixed solution of hydrofluoric acid and chromium trioxide aqueous solution with a concentration of 45-49%. The specific ratio and immersion time are based on the Schimmel etching solution in the GB / T 1554-2009 (current) standard for corrosion.

[0028] Comparative Example 6 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 10:1 solution, and the immersion time was 10 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0029] Comparative Example 7 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 10:1 solution, and the immersion time was 20 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0030] Example 2 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 10:1 solution, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0031] Example 3 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 10:1 solution, and the immersion time was 40 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0032] like Figure 2 As shown, Figure 2 (a) shows the appearance result of dislocation slip line under visual inspection lamp after corrosion in comparative example 5; Figure 2 (b) shows the results of the visualization of dislocation slip lines under a visual inspection lamp after corrosion in Comparative Example 6. Figure 2 (c) shows the appearance of dislocation slip lines under a visual inspection lamp after corrosion in Comparative Example 7; Figure 2 (d) shows the results of the visualization of dislocation slip lines under a visual inspection lamp after corrosion in Example 2. Figure 2 (e) shows the results of the visualization of dislocation slip lines under a visual inspection lamp after corrosion in Example 3.

[0033] It can be seen from the figure that the appearance of the dislocation slip lines in Examples 2 and 3 is comparable to that of the dislocation slip lines in chromium liquid corrosion in accordance with the national standard in Comparative Example 1. As the corrosion time decreases, the clarity of the dislocation slip lines in Comparative Examples 6 and 7 is poor and not obvious.

[0034] 3. Select a section of 8-inch B-doped <100> The silicon single crystal rod with a crystal orientation is continuously cut into silicon single crystal samples with a thickness of 2±0.2 mm. The sample numbers of this section of the single crystal rod from the tail to the head are 1 to 5, and they are cleaned with deionized water. Samples 1 to 5 are etched in accordance with the etching processes of the following comparative examples 8 to 11 and embodiment 4.

[0035] Comparative Example 8 The sample was immersed in a mixed solution of 65-68% nitric acid, 45-49% hydrofluoric acid and glacial acetic acid, HF:HNO3:HAc (volume ratio) = 10:1:0.2, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0036] Comparative Example 9 The sample was immersed in a mixed solution of 65-68% nitric acid, 45-49% hydrofluoric acid and glacial acetic acid, HF:HNO3:HAc (volume ratio) = 10:1:0.5, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0037] Comparative Example 10 The sample was immersed in a mixed solution of 65-68% nitric acid, 45-49% hydrofluoric acid, and glacial acetic acid, HF:HNO3:HAc (volume ratio) = 10:1:1, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the results after corrosion and determine the position and length of the dislocation slip line.

[0038] Comparative Example 11 The sample was immersed in a mixed solution of 65-68% nitric acid, 45-49% hydrofluoric acid, and glacial acetic acid, HF:HNO3:HAc (volume ratio) = 10:1:2, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the results after corrosion and determine the position and length of the dislocation slip line.

[0039] Example 4 The sample was immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 10:1 solution, and the immersion time was 30 minutes; a visual inspection light with a light intensity of ≥7klux was used to judge the corrosion results and determine the position and length of the dislocation slip line.

[0040] Figure 3 (a) ~ Figure 3 (d) is the appearance result of dislocation slip line under visual inspection lamp of comparative examples 8 to 11. Figure 3 (e) is the result of visualization of dislocation slip lines under a visual inspection lamp in Example 4.

[0041] Figure 4 (a) is a microscope image of the sample after corrosion in Comparative Example 8. Figure 4(b) is a microscope morphology image of the sample after corrosion in Example 4, and the magnification is 100X. Among them, the dislocation slip lines in Comparative Example 8 and Example 4 can be seen, but the surface state of the dislocation slip lines in Comparative Example 8 is poor, and all are corrosion pits. Compared with Example 4, it is more difficult to distinguish the dislocation slip lines.

[0042] Example 5 Select 8-inch B-doped <100> The silicon single crystal specimens with the same crystal orientation and thickness of 2±0.2mm were immersed in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, HF:HNO3 (volume ratio) = 10:1 solution, for 30min. The results after corrosion were judged using a visual inspection lamp with a light intensity of ≥7klux to determine the position and length of the dislocation slip line. The XRT test technology was used to scan and compare the differences between the results under the visual inspection lamp and the XRT test results.

[0043] Figure 5 (a) shows the visualization result of dislocation slip line under visual inspection light; Figure 5 (b) shows the XRT scanning results. The same sample was inspected in two ways, and the length and position of the dislocation slip line under the visual inspection light can be compared with the XRT morphology image.

[0044] Embodiment 6, 7 A large-diameter silicon single crystal sample with a known dislocation slip line was selected and continuously cut into silicon single crystal samples with a thickness of 4-10 mm, wherein the thickness of the sample in Example 6 was 4 mm and the thickness of the sample in Example 7 was 5 mm. The sample was immersed in a mixed solution of nitric acid with a concentration of 65-68% and hydrofluoric acid with a concentration of 45-49%, HF:HNO3 (volume ratio) = 10:1 solution, and the immersion time was 30 minutes; the result after corrosion was judged using a visual inspection lamp with a light intensity of ≥7 klux to determine the position and length of the dislocation slip line.

[0045] Comparative Example 12 The sample thickness in Comparative Example 12 is the same as that in Example 6, which is 4 mm. The sample is immersed in a mixed solution of hydrofluoric acid and chromium trioxide aqueous solution with a concentration of 45-49%, and the specific ratio and immersion time are based on the Schimmel etching solution in the GB / T 1554-2009 (current) standard for etching.

[0046] Comparative Example 13 The sample thickness in Comparative Example 13 is the same as that in Example 7, which is 5 mm. The sample is immersed in a mixed solution of hydrofluoric acid and chromium trioxide aqueous solution with a concentration of 45-49%, and the specific ratio and immersion time are based on the Schimmel etching solution in the GB / T 1554-2009 (current) standard for etching.

[0047] like Figure 6 As shown, Figure 6 (a) shows the appearance of dislocation slip lines under a visual inspection lamp after corrosion in Comparative Example 12; Figure 6 (b) shows the appearance of dislocation slip lines under a visual inspection lamp after corrosion in Example 6; Figure 6 (c) shows the appearance result of dislocation slip line under visual inspection lamp after corrosion in Example 7; Figure 6 (d) shows the results of the visual inspection of dislocation slip lines after corrosion in Comparative Example 13.

[0048] As can be seen from the figure, the length of the dislocation slip line in Comparative Example 12 is 28 mm; the length of the dislocation slip line in Example 6 is 25 mm; the dislocation slip line in Example 7 is only on the side; the dislocation slip line in Comparative Example 13 is only on the side. Compared with Comparative Example 12, the slip line length of Example 6 is reduced by 3 mm; the dislocation slip line in Example 7 is only on the side compared with Comparative Example 13. This is consistent with the rule that as the sample approaches the head of the silicon single crystal, the dislocation slip line gradually shortens.

[0049] In summary, the present invention provides a method for detecting dislocation slip lines of silicon single crystals, which is mainly aimed at silicon single crystals with a diameter greater than 300 mm and a dopant of element B. <100> For single crystal silicon, the main test item is dislocation slip line. The test method is simple and easy to implement. It uses a method that abandons the traditional chromium liquid for testing. It can eliminate interference factors under strong light, accurately identify dislocation slip line, and compare with XRT morphology map at the same time. It is an environmentally friendly method.

Claims

1. A method for detecting dislocation slip lines of a silicon single crystal, characterized in that: The following steps are involved: (1) Native <100> After the crystal orientation silicon single crystal is pulled, a sample with a thickness of 2-10 mm is cut and cleaned with deionized water; (2) Corrode the sample using a mixed solution, immerse the sample in a mixed solution of 65-68% nitric acid and 45-49% hydrofluoric acid, wherein the volume ratio of hydrofluoric acid to nitric acid in the mixed solution is HF:HNO3=10:1, and the immersion time is 30-40 min; (3) Use a visual inspection light to determine the corrosion results and the location and length of the dislocation slip line; (4) Use X-ray diffraction morphology to assist in the identification of samples.

2. The method for detecting dislocation slip lines of a silicon single crystal according to claim 1, characterized in that: The silicon single crystal has a diameter greater than 300 mm and the dopant is B element. <100> Crystal orientation silicon single crystal.

3. The method for detecting dislocation slip lines of silicon single crystal according to claim 1, characterized in that: In the step (1), the thickness of the sample cut is 4-10 mm.

4. The method for detecting dislocation slip lines of a silicon single crystal according to claim 1, characterized in that: In the step (3), a visual inspection light with a light intensity of ≥7 klux is used for visual inspection.

5. The method for detecting dislocation slip lines of silicon single crystal according to claim 1, characterized in that: In the step (4), when the sample thickness is less than 3 mm, XRT is used to determine the position and length of the dislocation slip line and compare them with the visual inspection results of the physical sample.

Citation Information

Patent Citations

  • Monocrystalline silicon dislocation corrosive agent and detection method

    CN103590113A

  • Dislocation identification method of silicon carbide crystal

    CN111238910A

  • Method for detecting axial dislocation defect of heavily boron-doped silicon single crystal

    CN117607150A

  • Methods for detecting defects in a single crystal silicon structure

    US20240255438A1

  • Method for detecting crystal defects in semiconductor silicon and detecting solution therefor

    US4243473A

Cited By

  • Identifying and analyzing equipment and distinguishing method for slip line and twin crystal

    CN120609852A